Abundance and genetic diversity of Quercus mulleri, microendemic, thretened species from Oaxaca - Pingarroni, Aline; Molina-Garay, Carolina; Rosas-Osorio, Carlos; Alfonso-Corrado, Cecilia; Clark-Tapia, Ricardo; Monsalvo-Reyes, Alejandro; Campos, Jorge E. (Instituto de Ecología, A.C., 2020)
Quercus mulleri is a microendemic oak from the Sierra Sur of Oaxaca and is considered in IUCN red list of threatened species as “critically endangered”, however, due to lack of current information on the species, the conservation status of its populations is unknown, and therefore it has not been possible to allocate an appropriate risk category to it. This work represents the first report of Q. mulleri after more than 60 years of its last taxonomic classification, with the aim to analyze its abundance, distribution and genetic diversity to propose conservation strategies. The species was re-localized, and we found that it is restricted to a small region in Sierra Sur and is fragmented and geographically isolated. Species populations have low individual frequency by size class (6.13 ± 5.6). Allelic diversity values, using five microsatellite regions from the quru-GA series, were low (AT=22 y Ao=4.4), but genetic diversity values were relatively high (Ho=0.54), suggesting that the population went through a bottleneck. Results indicate that Q. mulleri is a vulnerable species, and since in its distribution area there is an ongoing habitat loss plus its population fragmentation, its permanence could be at risk, and for this we recommend including this species in the Norma Oficial Mexicana 059 as “Species at Extinction Risk”.